2022
DOI: 10.3390/jfb13030154
|View full text |Cite
|
Sign up to set email alerts
|

Bone Abrasive Machining: Influence of Tool Geometry and Cortical Bone Anisotropic Structure on Crack Propagation

Abstract: The abrasive machining of cortical tissue is used in many arthroplasties and craniofacial surgery procedures. However, this method requires further research due to the processes’ complexity and the tissue’s composite structure. Therefore, studies were carried out to assess the impact of grid geometry and the anisotropic structure of bone tissue on the cutting process and crack propagation. The analysis was performed based on an orthogonal cutting in three directions. The grain shape has been simplified, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…According to recent studies, the Young's modulus of the osteon, interstitial matrix, and cement line is 20, 21.87, and 7.4 GPa, respectively [47]. These differences affect the nature of crack propagation, as confirmed by studies such as those by Bai et al [8] and Zawadzki and Talar [46].…”
Section: Orthogonal Cuttingmentioning
confidence: 87%
See 2 more Smart Citations
“…According to recent studies, the Young's modulus of the osteon, interstitial matrix, and cement line is 20, 21.87, and 7.4 GPa, respectively [47]. These differences affect the nature of crack propagation, as confirmed by studies such as those by Bai et al [8] and Zawadzki and Talar [46].…”
Section: Orthogonal Cuttingmentioning
confidence: 87%
“…The cutting depth of 25 μm was chosen based on previous experimental studies—this value provides the highest sensitivity to the influence of osteon orientation, minimizing disturbances caused by crack propagation [ 46 ]. To reduce the influence of thermal effects on the cutting process, a constant cutting speed of v c = 30 mm/min was maintained, which research has shown to prevent thermal necrosis at speeds below this value [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, there have also been very significant developments in recent years. In addition to the standard applications of surface topography measurements derived from tribology and related to plateau honed surfaces [44] or plasticity index [45], biotribological applications [46], primarily related to activities carried out on the human body, are increasingly appearing.…”
Section: Measurement Technologies For Metrology 40mentioning
confidence: 99%